(untitled) (Journal of Scientific Research, 2021)
This study focused to develop the fingerprint profile of Phyllanthus niruri through high performance thin layer chromatography. Various solvent extracts such as ethanol and water were prepared and phytochemical screening was made using standard procedures. The preliminary phytochemical analysis of two extracts of the plant showed the presence of secondary metabolites viz., alkaloids, triterpenoids, proteins, amino acids, flavonoids and steroids. The total flavonoid contents of leaves were significantly higher than those revealed in stem and root. The total phenolic contents of Phyllanthus niruri leaves (aqueous extract), leaves (ethanol extract) and root (ethanol extract) were 5.71 mg GAE/100 mg extract, 7.66 mg GAE/100 mg and 5.63 mg GAE/100 mg extract respectively. Methanol extract of Phyllanthus niruri was subjected to HPTLC analysis due to it is most effective, highly polar universal solvent for extraction of phytoconstituents. Among the samples, leaves extract resolved maximum number of spots followed by stem extract and root extract. It can be concluded that HPTLC fingerprinting of Phyllanthus niruri may be useful in differentiating the species from the adulterant and authentication of this herbal plant in the medical field and systematic plant studies.